THE APPLE VERSUS SAMSUNG PATENT LAWSUIT: AN ISSUE AND CRISIS MANAGEMENT APPROACH - Chan Tak Jie; Nurul Ain Mohd Hasan (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2017)
Crises are commonplace and it can be happened at any point of the organization process. Thus, it is worthwhile for the organization to identify the early plan of issue or potential risk occurring within organizations, as a small scale antagonist can pose a serious threat to the protagonist. Hence, it is not easy to win the reputation warfare. Thus, this paper aims to examine the crisis clusters in the Issue and Crisis Management Relational Model by applying on one of the cases which is Apple and Samsung patent lawsuit. The model suggested several stages which include pre-crisis management and post-crisis management. The discussion of the case will be surrounded on the two (2) clusters on the crisis management part, which include crisis event management and post-crisis management. The review of the case showed that Apple had won the lawsuit warfare and Samsung need to pay for the financial loss as a result of copying the design of the Apple’s product. In addition, the review also showed that the model need to be seen as an integrative approach, rather than as a sequence of process. This has called upon the management, especially the public relations or corporate communication department to look into the clusters that has been suggested to form a strategic solution to safeguard the organization’s reputation when the crisis strike